2020
DOI: 10.20944/preprints202007.0652.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Approach Towards Motion-Tolerant PPG-Based Algorithm for Real-Time Heart Rate Monitoring of Moving Pigs

Abstract: Animal welfare remains a very important issue in the livestock sector but monitoring animal welfare in an objective and continuous way remains a serious challenge. Monitoring animal welfare based upon physiological measurements instead of audio-visual scoring of behaviour would be a step forward. One of the obvious physiological signals related to welfare and stress is heart rate. The objective of this research was to measure heart rate (beat per minutes) on pigs with technology that soon will be affordable. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Nie et al also emphasized the challenges of transferring the PPG technique from human beings to livestock that whether the PPG theory based on skin blood perfusion is applicable for animals, and the similarities of skin between humans and animals need to be checked first. Youssef et al used PPG sensors on a pig's body to test whether it allows the retrieval of a reliable heart rate signal and concluded that the agreement between the PPG-based heart rate technique and the reference sensor was between 91% and 95% [31]. The reference also indicated that locations of the pig's body be chosen to place PPG sensor probe were important, because of their higher cutaneous perfusion and body fat.…”
Section: Related Workmentioning
confidence: 99%
“…Nie et al also emphasized the challenges of transferring the PPG technique from human beings to livestock that whether the PPG theory based on skin blood perfusion is applicable for animals, and the similarities of skin between humans and animals need to be checked first. Youssef et al used PPG sensors on a pig's body to test whether it allows the retrieval of a reliable heart rate signal and concluded that the agreement between the PPG-based heart rate technique and the reference sensor was between 91% and 95% [31]. The reference also indicated that locations of the pig's body be chosen to place PPG sensor probe were important, because of their higher cutaneous perfusion and body fat.…”
Section: Related Workmentioning
confidence: 99%
“…A significant part of wavelet signal analysis algorithms is based on the use of continuous wavelet transform [ 1 , 2 , 5 , 6 , 9 ]. The analysis of literary sources showed that wavelets are used in the analysis of signals such as electrocardiogram [ 13 , 14 , 15 , 16 ], electroencephalogram [ 6 , 17 , 18 ], seismic signals, signals from various sensors [ 1 ], etc.…”
Section: Related Workmentioning
confidence: 99%
“…The cardiovascular system is regulated by the autonomic nervous system and controls the physiological systems impacted by stress (Youssef et al, 2019). The vagal element of the autonomic nervous system regulates heart rate during stress in farm animals (Kovács et al, 2014).…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…The vagal element of the autonomic nervous system regulates heart rate during stress in farm animals (Kovács et al, 2014). Heart rate increases when animals are subjected to heat above their tolerance limits (Luz et al, 2015), so changes in heart rate can indicate physiological and psychological stress, disease, and coping strategies in animals (Youssef et al, 2019). Conventionally, Electrocardiogram (ECG) has been used to detect heart rate variability.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%